2019
DOI: 10.1002/hep.30279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Viral Genome Variability of Hepatitis B Virus–Induced Acute Liver Failure

Abstract: HBV GT-D and increased variability in HBV core, preS2 region and SHB are associated with a worse clinical outcome of acute HBV infection. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…All ALF patients presented with or developed sepsis and MODS. Interestingly, ALF patients were exclusively male, indicating that male sex may be a risk factor for ALF in SARS-CoV-2 infection, contrary to what has been shown for ALF due to other pathologies [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 90%
“…All ALF patients presented with or developed sepsis and MODS. Interestingly, ALF patients were exclusively male, indicating that male sex may be a risk factor for ALF in SARS-CoV-2 infection, contrary to what has been shown for ALF due to other pathologies [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 90%
“…DNA extraction was performed with QIAamp DNA mini kit (Qiagen). PCR for the whole HBV genome was performed as previously described [12]. For genotype assessment, detection of immune escape mutations and stop codon mutations in HBsAg the geno2pheno platform was used [17].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that viral factors, such as increased variability in HBV core, preS2 region, and HBsAg, as well as host factors (e.g., the presence of certain human leukocyte antigen (HLA) class II locus alleles), are associated with the development of ALF in the case of an acute HBV infection [12,13,14]. Furthermore, HBV reactivation has been shown to correlate with HBsAg mutations associated with enhanced capability to evade immune response, some of them were only present as minority variants as shown per next-generation sequencing (NGS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…There are 120 million carriers of HBV and 20 million patients with chronic hepatitis B 2 . A study showed 0.1%‐0.5% HBV‐infected patients would develop ALF 3 . HBV infection is a major risk factor for ALF patients.…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection is a major risk factor for ALF patients. However, current treatments for HBV‐ALF, which include antiviral treatment and other support measures, are not satisfying except liver transplantation 3 . But owing to dramatic clinical course and shortage of donor organ, many patients die during the waiting for the proper donor liver.…”
Section: Introductionmentioning
confidence: 99%